ANALISIS KEMAMPUAN BERPIKIR KREATIF MATEMATIS DITINJAU DARI SELF-EFFICACY DALAM MATERI LINGKARAN PADA SISWA SMP - Nora Noviyanti; Marhadi Saputro; Yudi Darma (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to analyze the relationship between students' mathematical self-efficacy and mathematical creative thinking ability on circle material at junior high school level. This research is a qualitative research and the method used in this research is descriptive method. The form of research used in this research is a case study. The setting of this research was conducted at SMP Negeri 1 Sungai Kakap. The subjects of this research were students of class VIII C SMP Negeri 1 Sungai Kakap who had studied circle material. The interviewed subjects consisted of 9 students based on high, medium, and low self-efficacy categories. The instruments used were self-efficacy questionnaire, mathematical creative thinking ability test, and interview. The data were analyzed qualitatively with the stages of data collection, data reduction, data presentation, and conclusion drawing. From the results of this study, it is concluded that students with high self-efficacy category have been able to solve the circle story problems appropriately and in accordance with the indicators of mathematical creative thinking ability. Students with moderate self-efficacy category are able to solve the circle story problems less precisely and correctly so that they have not been able to fulfill the three indicators of mathematical creative thinking ability. Students with low self-efficacy category are only able to provide one correct and appropriate answer in solving the Circle story problem, while other indicators of mathematical creative thinking ability cannot be completed correctly.